Shrub rainfall interception map based on Gash Model, Trail Valley Creek Watershed, Northwest Territories [Canada], 2018 - Chang, Qianyu; Zwieback, Simon; Berg, Aaron; DeVries, Ben
This dataset includes spatially distributed estimates of rainfall interception by birch shrub in an Arctic tundra area, the Trail Valley Creek watershed. The estimation map demonstrates the importance of rainfall interception in Arctic summer water balances, as well as the spatial variability in the amount of interception as controlled by the shrub leaf area index. The interception was estimated using the Gash interception model for sparse canopy, with climatic inputs from weather station records and shrub parameters derived from a satellite image. This dataset also contains the R script used for running and validating the model and producing the map.